(untitled) (Indian Journal of Child Health, 2015)
Objective: To study the effect of timing of cord clamping on the iron stores of infants born to anemic (hemoglobin [Hb] 7-10 g/dl) mothers, and if late clamping leads to polycythemia. Design: Randomized comparative trial. Setting: Tertiary care hospital in a metropolitan city. Participants: Term, healthy, and vaginally delivered neonates without any congenital malformations or birth asphyxia, born to booked anemic (Hb 7-10 g/dl) mothers having no medical or pregnancy-related complications were included in the study.Interventions: The pregnant mothers were randomized into three groups, and their umbilical cords were clamped at 1, 2, and 3 min. Neonatal hematocrit was estimated by the capillary method at 24 h of life, and infant’s (Hb) and ferritin were obtained at 3 months of life. Main Outcome Measures: Hematocrit at 24 h of life and serum iron and ferritin levels at 3 months of age. Results: The outcome variables significantly associated (p<0.05) with hematocrit were cord clamping time, maternal Hb and cord Hb, and ferritin. That associated with infant’s Hb were cord clamping time and cord Hb and ferritin. Whereas, only cord clamp time was significantlyassociated with infant’s ferritin. None of the neonates had polycythemia, and Hb and ferritin were found to be the highest in those whose cord was clamped at 3 min. Conclusion: In resource-constrained countries, where iron deficiency anemia is a major public health problem, delaying the umbilical cord clamping by up to 3 min will reduce the incidence of infantile anemia. It will serve as an additional cost-effective intervention in anemia control program without any adverse effect of polycythemia.